2004
DOI: 10.1176/appi.ajp.161.5.826
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Occupancy of Five Selective Serotonin Reuptake Inhibitors at Different Doses: An [11C]DASB Positron Emission Tomography Study

Abstract: At tolerable doses, SSRIs have increasing occupancy with increasing plasma concentration or dose. Occupancy of 80% across five SSRIs occurs at minimum therapeutic doses. This suggests that 80% 5-HTT blockade is important for therapeutic effect. Occupancy should be measured during development of antidepressant compounds targeting the 5-HTT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
390
5
2

Year Published

2004
2004
2009
2009

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 463 publications
(433 citation statements)
references
References 41 publications
27
390
5
2
Order By: Relevance
“…The doses of antidepressants used by Cavanagh et al are comparable those presented by Meyer et al, who demonstrated approximately 80% occupancy of 5-HTT by therapeutic doses of SSRIs (Meyer et al, 2004b).…”
Section: Discussionsupporting
confidence: 73%
“…The doses of antidepressants used by Cavanagh et al are comparable those presented by Meyer et al, who demonstrated approximately 80% occupancy of 5-HTT by therapeutic doses of SSRIs (Meyer et al, 2004b).…”
Section: Discussionsupporting
confidence: 73%
“…Lotrich et al (2005) (Figure 3) reported a mean plasma citalopram concentration of circa 10 ng/mL between 45 and 150 mins after an infusion of 10 mg citalopram in healthy control subjects. Meyer et al (2004) (Figure 1) measured a striatal SERT occupancy of about 50% for a plasma citalopram concentration of 10 ng/mL in subjects who had received daily oral doses of citalopram for 4 weeks. The same authors reported an occupancy of 80% across five SSRIs (including citalopram) at minimum therapeutic doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, brain SERT occupancy measured with PET after oral citalopram administration were reported Meyer et al, 2004). Our aim, therefore, was to in vivo characterise the blockade of the SERTbinding sites after citalopram infusion using [ 11 C]DASB as an imaging probe specifically binding to the SERT and to compare the results with those previously published after oral citalopram administration.…”
Section: Introductionmentioning
confidence: 99%
“…(Brücke et al, 1993;Pirker et al, 1995), it was suggested that both time points are reliably for measurements of SERTs with [ 123 I]b-CIT (Pirker (Pirker et al, 1995;Kugaya et al, 2003). Human PET studies using the SERT-selective radiotracer [ 11 C]DASB also showed high occupancy of SERTs in the midbrain and thalamus after (sub)therapeutic doses of various SSRIs (Meyer et al, 2004). In addition, previous studies in animals showed that [ 123 I]b-CIT binds to SERTs in these brain areas (Laruelle et al, 1993).…”
Section: Discussionmentioning
confidence: 99%